ELISA for Aging Biomarkers Induced by Telomere Dysfunction in Human Plasma. (25th November 2010) - Jiang, Hong; Chen, Wenqing; Qu, Lihui; Chen, Ying; He, Qiang; Wang, Huiping; Wu, Jianyong; Shou, Zhangfei; Ju, Zhenyu; Chen, Jianghua
Abstract : Background . We identified cathelicidin related antimicrobial protein (CRAMP) secreted from telomere dysfunctional bone marrow cells of late generation telomerase knockout mice (G4mTerc −/− ), increased in blood and various tissues. It can represented human aging and disease. The main aim of this study is to investigate the sensitive direct enzyme-linked immunosorbent assay (ELISA) method to analyze the human aging and disease in plasma and the detailed methods to quantify the direct ELISA of these aging biomarkers. Methods . Telomere lengths of 50 healthy persons are measured with real-time PCR in blood cells. Plasma samples from all subjects are analyzed using direct ELISA. Results . From 25 years old person to 78 years, the telomere length becomes shorter during aging. In blood plasma, the expression levels of CRAMP increases during human aging. There is the reverse correspondence between the telomere length and the plasma CRAMP level. We also find that the fresh plasma, the frozen plasma which thawed less than 3 times, and the plasma kept in the room temperature less than 3 hours are better for the ELISA analyze of CRAMP in the plasma. Conclusion . This CRAMP ELISA could become a powerful tool for investigating the relationship between human aging and telomere length shortening.